Strategi Tabligh Gus Nur - Sarah Maesaroh (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2016)
This research reveals about Gus Nur planning on tabligh by using grave media, actualizing / performing tabligh activities, and how feedback from Gus Nur tabligh activity. Researchers use descriptive analysis method with qualitative approach. From the result of research that Gus Nur planning include the introduction of audience so that message delivered can influence congregation, use media and method that have harmony can invite attention of pilgrims. Implementation of tabligh in the form of lectures from the podium continued in the grave with the use of shroud and keranda as a visualization of the dead. Feedback received in the form of instantaneous and delayed feedback that is positive and negative. The positive feedback received is to thank Gus Nur who became the way of Allah's guidance so repent. Negative feedback in the form of accusations of magic, heresy, shirk, kafir and misleading. From the feedback that appears, he replied from the book “Dakwah dari dalam Kubur” and facebook